2014
DOI: 10.1098/rsif.2013.0884
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar dynamics of a connected chain of active, polar, Brownian particles

Abstract: We show that active, self-propelled particles that are connected together to form a single chain that is anchored at one end can produce the graceful beating motions of flagella. Changing the boundary condition from a clamp to a pivot at the anchor leads to steadily rotating tight coils. Strong noise in the system disrupts the regularity of the oscillations. We use a combination of detailed numerical simulations, mean-field scaling analysis and first passage time theory to characterize the phase diagram as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(168 citation statements)
references
References 32 publications
9
156
3
Order By: Relevance
“…Experiments reveal the resulting buckled shape is determined by the strength and type of surface defect or pinning 17,22 . Buckling instabilities have also been observed in simulations of a variety of models of pinned or clamped motility assays filaments 22,[24][25][26][27] . Recent Brownian dynamics simulations also found buckling instabilities in follower-force propelled filaments pushing a cargo 28 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Experiments reveal the resulting buckled shape is determined by the strength and type of surface defect or pinning 17,22 . Buckling instabilities have also been observed in simulations of a variety of models of pinned or clamped motility assays filaments 22,[24][25][26][27] . Recent Brownian dynamics simulations also found buckling instabilities in follower-force propelled filaments pushing a cargo 28 .…”
Section: Introductionmentioning
confidence: 88%
“…Fatehiboroujeni et al 46 studied the double-clamped 3D case, in which both ends of the filament are clamped and the base state is pre-buckled. Chellakot et al 27 studied a slightly different problem with noisy follower forces using a bead-spring model (discussed further in section 5) and found β db ≈ 36 and β hb ≈ 78 in the weak (but finite) follower force noise regime. Reference 27 also discusses the β 4/3 growth of the frequency in both pinned and clamped filaments, however they find it no longer holds at very large β .…”
Section: Related Constrained Follower-force Problemsmentioning
confidence: 99%
“…For a polymer, activity can be interpreted in two ways. On the one hand, our polymer can be considered as comprised of active monomers, e.g., active Brownian particles [21,22,35,36,38,40]. On the other hand, the active force may originate from interactions with uncorrelated surrounding ABPs, hence, the polymer corresponds to a passive polymer dissolved in an active bath [30,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of individual active filaments either pivoting or freely swimming showed that activity can drive conformational transformations [48], such as spiralling and spontaneous beating [42,49,50], both in the presence and absence of hydrodynamic interactions. Balancing the bending moment with the torque produced by the active force shows [49,50] that activity increases the tendency of the filament to buckle, thus reducing its persistence length. Similar effects have also been observed in models that treat activity as timecorrelated random forces [51][52][53].…”
Section: Introductionmentioning
confidence: 99%